FORMATION OF LOCAL SELF-GOVERNMENT IN POLAND IN THE CONTEXT OF ADMINISTRATIVE-TERRITORIAL REFORM: ESTIMATION OF EXPERTS - Бровко, О. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The  article  deals  with  the  formation  of  local  self-government  in  Poland  during  gmina  and administrative-territorial  reform. The basic  stages of  reforms and  the most meaningful  changes  in local self-government of Poland, that took place because of reformation, are analysed. Moreover, the author answers the question of how the entering of Poland into UE influenced the process of forming local  self-government.  Basic  problems,  that  were  not  overcame  as  a  result  of  reform  and  new problems  that  arose  up  as  a  result  of  the  realization  of  reform  are  determined.  The  research  is undertaken on  the basis of deep  interviews with  the  leading Polish experts  in  the field of  local self-government.